BeBe braille browser - Aberion, Ma. Darlyn S.; Edillor, Juven Roberto R.; Gonzales, Ma Theresa B.; Sy, Marvin L. (2003)
Today's world is rapidly changing, everyday bounds are being crossed to something better. Even as you are reading this, some young Einstein is discovering another breakthrough for tomorrow. In pursuit for the betterment of our present, the researchers have taken steps to make this thesis both technologically progressive and relevant. As such, they have undertaken studies to make one of the most powerful and useful tools of to those who are physically challenged. The Internet of the World Wide Web is a potent means for information gathering, communication and entertainment, unfortunately not all have the means to accessing it. Visually impaired people have to buy specialized equipment for them to be able to do basic things that sighted people can with their computers. Aside from being expensive, these apparatuses are usually hard to use. Realizing such, the research is focused on developing application software that will enable visually impaired people to "see" what is happening on the web. Seeing that the main obstacle here is to present web content to the visually impaired in a format they can easily recognize, they have decided to use the medium of sound and touch in relaying the information to the user. The researchers created a relatively platform independent either through aural relay (sounds) or Braille output (touch). Another important feature that they took into consideration is ease of use. Thus, they provided speech input using a speech recognizer and the use of hot keys to access vital software functions.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Computer programs; Text to speech software; BeBe (Computer program).; Braille browser; text to speech program